2005
DOI: 10.1002/em.20184
|View full text |Cite
|
Sign up to set email alerts
|

Increased sensitivity to mitomycin C‐induced sister chromatid exchange in lymphocytes from patients undergoing hyperbaric oxygen therapy

Abstract: Treatment of cells with hyperbaric oxygen (HBO) results in the generation of reactive oxygen species and the induction of DNA damage. In the present study, we have evaluated the sister chromatid exchange (SCE) frequencies in lymphocytes from patients undergoing hyperbaric oxygen therapy (HBOT). In addition, we have determined the sensitivity of lymphocytes from those patients to SCE induction by 20 and 40 ng/ml mitomycin C (MMC). Patients undergoing HBOT for diabetic feet were exposed to 10 consecutive daily H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Determination of the SCE frequency was performed by the method described previously (Duydu et al, 2006;Eken et al, 2005). Lymphocytes from 300 mL of blood were cultured in RPMI 1640 (Biological Industries, Israel) medium supplemented with 20% fetal calf serum (Seromed, Germany), 2% phytohemagglutinin (Sigma) and L-Glutamine (Sigma) and kept in the dark at 37 C for 72 hours.…”
Section: Cytogenetic Assaysmentioning
confidence: 99%
“…Determination of the SCE frequency was performed by the method described previously (Duydu et al, 2006;Eken et al, 2005). Lymphocytes from 300 mL of blood were cultured in RPMI 1640 (Biological Industries, Israel) medium supplemented with 20% fetal calf serum (Seromed, Germany), 2% phytohemagglutinin (Sigma) and L-Glutamine (Sigma) and kept in the dark at 37 C for 72 hours.…”
Section: Cytogenetic Assaysmentioning
confidence: 99%
“…Many studies have reported that exposure to genotoxic agents, such as reactive oxygen species, influences the cytogenetic endpoints of cultured lymphocytes, and, in addition, it determines the sensitivity of lymphocytes in vitro from subjects exposed to genotoxic agents such as X-rays, ultraviolet light, bleomycin or mitomycin C [8][9][10]. The cytogenetic characterisation and classification of the different types of chromosomal aberrations in human peripheral blood lymphocytes have an important role in human genetics.…”
mentioning
confidence: 99%
“…MMC acts on the DNA and increases SCEs, induced in specific chromosomal regions, as it has been reported that MMC increases SCEs mainly at fragile chromosome domains (Wenger, 1995). MMC has been extensively used in chromosomal fragility studies in order to investigate if some conditions, such as diseases and various physical, chemical and biological agents affect its mutagenic efficiency (Latt et al, 1975;Ohtsuru et al, 1980;Duydu et al, 2006;Digkas et al, 2010 a ). The existence of sister chromatid exchanges (SCEs) connects to DNA replication, and their analysis is an excellent tool for the quantitative and qualitative evaluation of the DNA damage caused by physical, chemical or biological mutagenic agents (Lialiaris et al, 1987;Lialiaris et al, 2010;Digkas et al, 2010 b ).…”
Section: Introductionmentioning
confidence: 99%